FRAUD TRIANGLE PADA PERILAKU KECURANGAN AKADEMIK (Studi Pada SMK Negeri 10 Surabaya) - Ririt Ariani; Arin Yuni Pusporini; Hero Priono (Jurnal MEBIS (Manajemen dan Bisnis), 2022)
This study aims to determine the factors that influence academic fraud behavior of students of SMK Negeri 10 Surabaya. The population in this study is all students of class XI Accounting at SMK Negeri 10 Surabaya academic year 2016-2017 which amounted to 116. Determination of samples using Slovin technique obtained sample size as much as 90. Data analysis used is path analysis withSPSS 23. The results of this study indicated that pressure does not affect academic fraud behavior. Opportunity and rationalization have a positive effect on the academic fraud behaviors of the students of SMK Negeri 10 Surabaya.